The Life Cycle Assessment of Cement Product with Alternative Fuels Usage in Indonesia - Arief Setiawan; Moh. Yanuar Jarwadi Purwanto; Kiman Siregar (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2021)
The aim of this study was performed a life cycle assessment in cement production. In order to gain improvement on environmental impact therefore the assessment should find the hotspots. The improvement is expected to find better fuel composition to reduce its impact by using variant of alternative fuels. The scope of study covers mining extraction to processing of cement (cradle to gate). The study results showed the value of 1 ton of cement : global warming potential impacts is 760.11 kg CO2-eq, acidification potential 1.32 kg SO2-eq, photochemical oxidant creation potential 0.0508 kg C2H4-eq, human toxicity potential 123.97 kg 1.4-DB-eq and abiotic depletion potential 2181.75 MJ. The data show that the highest contributor of impact is kiln unit. The energy used in kiln process unit contributes 92.46% of the total energy intensity in the cement production process. The results show that the energy required to produce 1-ton cement product is 3.27 GJ with the kiln process unit having the highest energy used contribution with a value of 3.03 GJ / ton product. The study has comprised four scenarios in order to acknowledge the best recommended practice of fuel compositions in the hotspots area.